Prevalence of Hysterectomy by Self-Reported Disability Among Canadian Women: Findings from a National Cross-Sectional Survey - Natalie V. Scime; Hilary K. Brown; Amy Metcalfe; Erin A. Brennand (Mary Ann Liebert, 2021)
Introduction: Our objective was to investigate differences in prevalence of hysterectomy by self-reported disability status among Canadian women. Materials and Methods: We analyzed cross-sectional data from the Canadian Community Health Survey 2012 on 30,170 women aged ?20 years. Disability was defined as reports of sometimes or often (vs. never) experiencing functional limitations or reduction in daily activities at home, school, or work. Frequency of these limitations was used as a proxy for disability severity. The outcome was self-reported hysterectomy status. Modified Poisson regression was used to quantify the prevalence ratio (PR) and 95% confidence interval (CI) for hysterectomy according to any, functional, or activity-limiting disability, after adjustment for household income, employment, education, ethnicity, and marital status. Results were stratified by age at time of data collection, categorized as childbearing (20?44 years), perimenopausal (45?59 years), and postmenopausal (60 years and older). Results: Disability was significantly and consistently associated with higher prevalence of hysterectomy in women. The strength of association was inversely related to age category, and PRs for a given age category were similar across disability types and severity levels. PRs for the association between any disability and hysterectomy were 2.18 (95% CI 1.36?3.50) for childbearing-aged women, 1.48 (95% CI 1.21?1.80) for perimenopausal women, and 1.12 (95% CI 1.02?1.24) for postmenopausal women. Conclusions: Prevalence of hysterectomy is disproportionately higher among women with self-reported disabilities compared with women without disabilities, with these differences most pronounced in women of childbearing age.